2022
DOI: 10.1038/s41375-022-01708-9
|View full text |Cite
|
Sign up to set email alerts
|

DDX41 coordinates RNA splicing and transcriptional elongation to prevent DNA replication stress in hematopoietic cells

Abstract: Myeloid malignancies with DDX41 mutations are often associated with bone marrow failure and cytopenia before overt disease manifestation. However, the mechanisms underlying these specific conditions remain elusive. Here, we demonstrate that loss of DDX41 function impairs efficient RNA splicing, resulting in DNA replication stress with excess R-loop formation. Mechanistically, DDX41 binds to the 5′ splice site (5′SS) of coding RNA and coordinates RNA splicing and transcriptional elongation; loss of DDX41 preven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Qin et al [ 60 ] overexpressed DDX41 in HeLa cells, and RNA-seq revealed that DDX41 regulates transcription and alternative splicing of genes involved in tumorigenesis and immune response. Recently, Shinriki et al [ 61 ] discovered that DDX41 mainly binds 5′ splice sites of coding RNA, indicating its role in forming activated spliceosomes ( Figure 3 ). Nevertheless, further studies are warranted to address how DDX41 executes its role in pre-mRNA splicing, especially related to its helicase activity.…”
Section: Functions Of Ddx41mentioning
confidence: 99%
See 3 more Smart Citations
“…Qin et al [ 60 ] overexpressed DDX41 in HeLa cells, and RNA-seq revealed that DDX41 regulates transcription and alternative splicing of genes involved in tumorigenesis and immune response. Recently, Shinriki et al [ 61 ] discovered that DDX41 mainly binds 5′ splice sites of coding RNA, indicating its role in forming activated spliceosomes ( Figure 3 ). Nevertheless, further studies are warranted to address how DDX41 executes its role in pre-mRNA splicing, especially related to its helicase activity.…”
Section: Functions Of Ddx41mentioning
confidence: 99%
“…Using a zebrafish Ddx41 loss-of-function mutant, Dr. Teresa Bowman's group recently found that R-loop levels increase nearly two-fold in Ddx41 mutants [ 74 ]. Increased R-loops are also observed in DDX41-KD or by DDX41 inhibitor in K562 cells [ 61 ]. Recently, Dr. Karlene Cimprich's lab found that R-loops bind and activate cGAS in the cytoplasm [ 77 ], while our laboratory [ 55 ] and another group [ 68 ] found that DDX41 functions in the upstream of cGAS–STING.…”
Section: Functions Of Ddx41mentioning
confidence: 99%
See 2 more Smart Citations
“…The pleiotropic effects of disrupting spliceosomal components often make it difficult to untangle the different pathogenic mechanisms; for example, SF3b1 also contributes to malignancy through R-loop formation and DNA damage ( Singh et al 2020 ). DEAD-box helicase DDX41 is another spliceosome-associated protein linked to cancers, and its disruption causes changes to both splicing and R-loop formation, leading to replicative stress ( Shinriki et al 2022 ). sacy-1 , the Caenorhabditis elegans homolog of DDX41, also has multiple roles; it was initially identified in a screen for oocyte meiotic maturation factors (the name sacy-1 stands for “suppressor of acy-4 ”) ( Kim et al 2012 ), and was only later understood to be involved in splicing and to be associated with C complex proteins ( Tsukamoto et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%